PENGARUH PERANAN AUDIT INTERNAL TERHADAP PENERAPAN GOOD CORPORATE GOVERNANCE (STUDI KASUS PADA PG REJO AGUNG MADIUN) - subagijo subagijo (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2014)
The role of internal audit will be more reliable in developing and maintaining the effectiveness of the internal control system, risk management and good corporate governance in order to sustain the realization of a healthy company. Good corporate governance practices can enhance corporate value by enhancing financial performance, which may reduce the risk undertaken by the council decisions that benefit themselves. The purpose of this study was to determine the effect of the role of internal audit of the implementation of good corporate governance in the Great rejo PG Madiun by spreading the core questions to all employees of the Internal Control Unit number 34. The data was compiled and analyzed using the software Statistical Programme for Social Sciences (SPSS) version 17 for windows to calculate the value of the regression, both simple linear regression. The results obtained from this study indicate that the role of internal audit and a significant positive effect on the implementation of good corporate governance in the Great Redjo PG Madiun as evidenced by the results of a significance value of 0.000 with a simple linear regression equation Y = 15,550 + 0,707X + e.